Improved Maleic Anhydride Grafting to Linear Low Density Polyethylene by Microencapsulation Method - Iman Rahayu; Achmad Zainuddin; Sunit Hendrana (Universitas Gadjah Mada, 2020)
A common graft copolymerization method usually results in a low degree of grafting due to its poor inter-component interactions. A monomer microencapsulation method should be useful to enhance the current graft copolymerization technique. The maleic anhydride (MAH) grafted with linear low-density polyethylene (LLDPE) was successfully synthesized by monomer microencapsulation without using a direct method in order to find a high degree of grafting. The results showed that the degree of grafting of the LLDPE synthesized by microencapsulation (5.9%) was higher than that achieved with the direct method (5.0%).